Performance of different abrasive materials during abrasive water jet machining of glass - Khan, Ahsan Ali; Haque, Md. Mohafizul (Elsevier BV, 2007)
Different types of abrasives are used in abrasive water-jet machining like garnet, aluminum oxide, olivine, silica sand, silicon carbide, etc. The present work gives a comparative analysis of the performance of garnet, aluminum oxide and silicon oxide during abrasive water-jet machining of glass. The study showed that width of cut increases as the stand-off distance of the nozzle from the work is increased which is due to divergence shape of the abrasive water-jet. However, the garnet abrasives produce the smallest width of cut followed by aluminum oxide and silicon carbide. This is because of higher hardness and cutting ability of silicon carbide followed by aluminum oxide and garnet. It was also noticed that width of cut reduces with the increase of feed rate. With the increase in work feed rate, the work is under the jet for a shorter time which causes a smaller width of the slots. Again, width of cut was found to be the smallest while using garnet abrasives followed by aluminum oxide and silicon carbide. The taper of the cut slot was found to be higher at a greater stand-off distance and work feed rate, but smaller at a higher pressure. Since silicon carbide is very hard, it maintains its cutting ability as the abrasives move down. As a result, the difference of the width at the jet entrance and the jet exit is not significant. This causes a smaller taper of the cut slots. The width of the cut slot was found to increase with increase in jet pressure. At a higher jet pressure the kinetic energy of the abrasives increases, resulting an enhanced cutting ability of the abrasives and causes widening of the cut slots. Due to higher hardness, silicon carbide produced the maximum width of cut followed by aluminum oxide and garnet.